Anglo-American Relations at the Paris Peace Conference of 1919 - Tillman, Seth P. (Book collections on Project MUSE., 1961)
The year 1919 marks a high point in the world power and prestige of Western democracy. World War I was ended, and the victory belonged to the democratic states. Theirs was the sober task-and the unique opportunity-of formulating a settlement that would guarantee impartial justice and preserve the peace. Dr. Tillman examines here the documentary account of Anglo-American diplomatic relations during this critical period. He shows the interaction of personalities in both governments, the patterns of cooperation and conflict as they negotiated major issues of war and of peace, and the political repercussions in both England and America that led either to compromise or to defeat of some of the best purposes of the Versailles Treaty. Originally published in 1961. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.